Interleukin in endometriosis-associated infertility-pelvic pain: systematic review and meta-analysis. Issue 1 (July 2019) - Malvezzi, Helena; Hernandes, Camila; Piccinato, Carla A; Podgaec, Sérgio
Abstract : The objective is to study the significance of altered interleukin levels in endometriosis-related infertility or pelvic pain. The present systematic review and meta-analysis includes a discussion on the roles of interleukin in the physiopathology of endometriosis-associated infertility and/or pelvic pain. We included all studies in which interleukins in peritoneal fluid, follicular fluid or serum from patients were measured and that correlated the findings with either peritoneal or deep endometriosis-associated infertility or pelvic pain. For the meta-analysis, we selected studies on the following cytokines: interleukin-1 (IL-1), interleukin-6 (IL-6) and interleukin-8 (IL-8). Endometriosis is a chronic inflammatory disease. Inflammatory processes clearly participate in the etiology of endometriosis. Cytokines are mediators of inflammation, and increase in their concentration in plasma or other body fluids signals the presence and extent of tissue lesions. A number of studies have reported on the association between higher cytokine levels and progression or maintenance of endometriosis and coexisting infertility or pelvic pain. The results of the analyses support that an association exists between elevated serum IL-6 and/or IL-8 concentrations and the occurrence of endometriosis-associated infertility. Such association was not found for endometriosis-associated pain. In spite of accumulated evidence on the association of pro-inflammatory cytokines and endometriosis, it still is not clear if and how these mediators participate in the physiopathology of endometriosis-associated infertility or pelvic pain, in part due to poor quality of the evidence established in the vast majority of interleukins and challenges in endometriosis research reproducibility. In summary, the results of the analyses support that an association exists between elevated serum IL-6 and/or IL-8 concentrations and the occurrence of endometriosis-associated infertility.